The situation of the woman in the socialistic countries today - Salles, Maria do Rosário Rolfsen (Universidade Estadual Paulista / UNESP, 2009)
This article intends to deal with some characteristics of the woman's work conditions and everyday life in two socialistic countries (URSS and PPR), in order to discuss the persistence of some contradictions between house-keeping and professional work, whithin the historical background of women's liberation and the increase of feminine participation in labour force.